When Incentives Backfire: Spillover Effects in Food Choice - Manuela Angelucci; Silvia Prina; Heather Royer; Anya Samek (Institute for the Study of Labor (IZA), 2015)
How do peers influence the impact of incentives? Despite much work on incentives, little is known about the spillover effects of incentives. We investigate two mechanisms by which these effects can occur: through peers' actions and peers' incentives. In a field experiment on snack choice (grapes versus cookies), we randomize who receives incentives, the fraction of peers incentivized, and whether or not it can be observed that peers' choices are incentivized among over 1,500 children in the school lunchroom. Incentives increase the likelihood of initially choosing grapes. However, peer spillover effects can be large enough to undo these positive effects.
Keywords: C93; I1; J13; 330; food choice; incentives; spillovers; field experiment